Some Recent Developments in Futures Hedging - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 2002)
The use of futures contracts as a hedging instrument has been the focus of much research. At the theoretical level, an optimal hedge strategy is traditionally based on the expected–utility maximization paradigm. A simplification of this paradigm leads to the minimum–variance criterion. Although this paradigm is quite well accepted, alternative approaches have been sought. At the empirical level, research on futures hedging has benefited from the recent developments in the econometrics literature. Much research has been done on improving the estimation of the optimal hedge ratio. As more is known about the statistical properties of financial time series, more sophisticated estimation methods are proposed. In this survey we review some recent developments in futures hedging. We delineate the theoretical underpinning of various methods and discuss the econometric implementation of the methods. [ABSTRACT FROM AUTHOR]